The Securitization and Commodification of the Consumer-Citizen: Biopolitics of the Credit Card Industry - Nyyssonen, Katrina (University of Waterloo, 2018)
This thesis examines the biopolitics of the credit card industry and its governance of consumers through consumer-citizenship obligations and the transformation of consumer data into valuable information commodities. Biometrics and transactional data trails or ‘data doubles’ are used to securitize identity, define responsible citizenship, and to delimit rights and access to valuable social resources. Binding data to consumer-citizens enables the credit card industry to exercise biopower over consumer subpopulations through social sorting based on categories of risk and value. Subpopulations are then both acted upon and sold to third parties as ‘valuable information commodities.’ This thesis analyzes Visa and Mastercard Canadian credit card policies to determine how the consumer-citizenship is constituted and the extent to which Canadian federal legislation (Personal Information Protection and Electronic Documents Act enable) enables or constrain credit card companies exercise of biopower over consumer populations. This thesis concludes that credit card companies enact a form of biopolitical governance-at-a-distance through entrepreneurship and responsibilization. Corporate policies enable the aggregation and commodification of personal information, for purposes not explicitly made known to customers, in order to drive economic growth for the credit card industry and its ‘third parties.’